The level of positive thinking among parents of autistic children ))A field study in Lattakia)) - بدور, لينا; عيسى, زينة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is know the level of positive thinking among parents of autistic children in the city of Lattakia, and to identify the differences in the level of positive thinking between them according to the gender variable. To achieve this goal, the researcher used the descriptive approach, and prepared the positive thinking scale, and after making sure of its validity and consistency, it was distributed to a sample of (40) fathers and mothers from the families of autistic children in the city of Lattakia. The results of the research showed that the level of positive thinking among parents is high, and the most common dimensions came in the following order (positive feelings first, then after positive self-concept, positive resilience, life satisfaction, and finally positive expectations), and the results of the research also showed the absence of A statistically significant difference between parents in the level of positive thinking.